Resveratrol-loaded gold nanoparticles enhance caspase-mediated apoptosis in PANC-1 pancreatic cells via mitochondrial intrinsic apoptotic pathway - Dong Gun Lee; Mindong Lee; Eun Byeol Go; Namhyun Chung (Cancer Nanotechnology, 2022)
Abstract Background Pancreatic ductal adenocarcinoma (PDAC) remains one of the most fatal malignancies. Several chemotherapies employing fluorouracil (5-FU) and gemcitabine were attempted, but the survival rate was extremely low. Resveratrol (RVT), known as a polyphenol compound and phytoalexin, was demonstrated to induce intrinsic apoptosis in cancer cells. However, its low delivery performance and efficiency at tumor sites remain an obstacle to exploit RVT as a drug. To address these problems, we bio-conjugated resveratrol with gold nanoparticles (GNPs) via polyvinylpyrrolidone as a cross-linker (RVT@PVP-GNPs) and investigated whether the fabrications could enhance the delivery performance and anti-tumor efficacy of RVT. Results The fabrication of gold nanoparticles (GNPs) and bio-conjugated with resveratrol (RVT@PVP-GNPs) was conducted firstly. TEM image, spectrophotometry and zeta-potential revealed that the GNPs and RVT@PVP-GNPs having a size of approximately 40 nm were successfully synthesized and exhibited moderate stability. GNPs alone represented no damage in PANC-1 cells and moreover diminished the cytotoxicity of RVT in Raw264.7 murine macrophage cells, demonstrating the superiority of gold nanoparticles as a drug carrier. Evaluation using dialysis showed a burst release rate of RVT within 96 h at pH 5.0, demonstrating the possibility of enhanced efficiency of RVT delivery through blood vessels to the tumor. The RVT@PVP-GNPs induced increased rates of S-phase cell cycle arrest and apoptosis compared with free RVT. Notably, RVT@PVP-GNPs diminished the proportion of necrotic cells, whereas free RVT increased it. We also demonstrated that the RVT@PVP-GNPs may induce an apoptosis via intrinsic mitochondria with higher degree compared with free RVT, indicating the possibility of enhanced anti-tumor agents. In animal studies, RVT@PVP-GNPs conjugated with AS1411 aptamer induced efficient tumor volume suppression without accumulation in or damage to the kidneys in vivo. Conclusions The results demonstrate that RVT@PVP-GNPs enhance the anti-tumor efficacy of free RVT by activating the intrinsic apoptotic pathway and could be considered as potential anti-tumor drug candidates against pancreatic cancer cells.